Pengelolaan Keuangan sebagai Panduan Menghadapi Tantangan - Fitrah, Muhammad; Ashar, A. Ihsan; Rifani, Riza Amalia (Amsir Community Service Journal, 2025)
Community service highlights the importance of providing maximum benefits to society. This activity discusses the implementation of community service, focusing on seven forms of service, including direct services. The initiative also underscores the strategic role of Micro, Small, and Medium Enterprises (MSMEs) in the Indonesian economy, with significant contributions and resilience in facing economic challenges. Community service in Cendana Village involves enthusiastic MSME entrepreneurs committed to developing their businesses through basic business management training. Needs analysis indicates a push for a deeper understanding of entrepreneurship and marketing strategies, addressed through seminars and entrepreneurship training. The program includes observing the potential of MSMEs, delivering tailored content, and employing training methods such as lectures, Q&A sessions, and post-training follow-up plans. Participants, especially female MSME owners, gain insights into effective financial management, emphasizing the importance of separating personal and business expenses. The acquired financial management skills are expected to enhance the effectiveness and efficiency of MSMEs, supporting better decision-making.